Interest-Free Treasury Bonds (IFTB): Islamic Finance and Legal Clarifications - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
Purpose: Although the treasury bill is the essential monetary instrument in central banking operations, its application in Islamic banking is not legitimate because it involves usury. This implies that the system cannot apply monetary and fiscal policies. To remove this obstacle “Interest-Free Treasury Bond” (IFTB) is introduced as a substitute for conventional treasury bills.Design: IFTB is a valuable paper which is issued by government treasury through a barter contract and is sold to central or commercial banks. The issuer is a debtor to the holder, and has to pay back the nominal value at maturity to the holder; in addition, the issuer is committed to lending a similar amount of money to the paper holder for an equal period. The Shariah and legal background of IFTB is explained through new contract types of “time-barter contract” and “time-loan contract”.Finding: IFTB is a zero-coupon, asset-backed note with no interest and is designed upon “debt equal to future loan”, or “loan equal to future debt” with “time-withdrawal right”. The paper holder can supply and transact her bond in the secondary market at a competitive price.Practical Implication: It can be used as a substitute for conventional treasury bills. All traditional and non-usury systems can implement IFTB.JEL: E43, E44, E52, E58, E62, E63